Exploring the Role of Workplace Empowerment on Organizational Commitment of University Female Teaching Staff: Evidence from One Private University in Cambodia - Channarika, Kan; Mardy, Serey (MultiTech Publisher, 2024)
This study was designed to explore the role of workplace empowerment on the organizational commitment of female teaching staff in the university by using the qualitative survey method. The sample of the study was selected by using a purposive sampling technique and it comprised of 10 female university teachers. Two interview protocols, one each for workplace empowerment and organizational commitment were used to collect the data and thematic analysis was applied to analyze the participants’ interview transcripts. The results of the present study assist the prior research that workplace empowerment is the main contributor of organizational commitment. The results showed that teachers have a very little level of workplace empowerment as a result they were committed to a personal level of interest rather than that of organizational support. The study suggested that institutions should create an environment to enhance the perceptions of empowerment among employees that will positively influence them and it will eventually increase the institution's effectiveness and commitment.